Mechanical strength problem of thin silicon wafers (120 and 140 μm) cut with thinner diamond wires (Si kerf 120 → 100 μm) for photovoltaic use. (15th November 2020) - Sekhar, Halubai; Fukuda, Tetsuo; Tanahashi, Katsuto; Takato, Hidetaka; Ono, Hiromichi; Sampei, Yoshiyuki; Kobayashi, Tsubasa
Abstract: We compared the mechanical strength of as-sawn thin silicon wafers (120 and 140 μm) cut by thinner diamond wires (Si kerf 120 → 100 μm). The fracture strength was evaluated by applying uniaxial mechanical loads on the fresh- and worn-wire sides of the wafers. The loads were applied parallel and perpendicular to the direction of the wire saw marks. Under parallel loading, wafers from both the fresh- and worn-wire sides had approximately the same low fracture strength, whereas under perpendicular loading, wafers from the fresh-wire side had a larger strength distribution compared to that of wafers from the worn-wire side. Observation by laser microscope revealed deeper pits in the lower strength wafers compared to the higher strength wafers. Observation by ion milling and subsequent scanning electron microscope revealed several cracks below the deeper pits whereas few cracks appeared below the shallower pits. Since the cracks were thought to be the deciding factor in the wafer fracture, we conducted a fractographic study on the fractured surfaces from the perspective of crack propagation. We found that the mechanical strength of the wafers cut by thinner wires showed a larger strength distribution. Although this variation was probably caused by the motion of the thin wire during the sawing process, further study is required for confirmation. Graphical abstract: As developed thin diamond wire As diamond wire sawn (DWS) thin (100 μm) Si (DW-80d-M6/12). Wafer (saw damage 20 μm etched). Image 1 Highlights: The wafer sawing industry mainly focuses on increasing the number of Si wafers obtained from per-kg of Si bricks by reducing both wafer thickness and kerf loss per wafer. In multi-wire sawing, the diamond wire quality has strong impact on thin wafers fracture strengths and sawing yields. The diamond wire quality is improved by considering diamond particles are small in size, uniformly coated with less agglomeration on the wire. The improvements in diamond wire quality allows us to reduce crack depths on fresh (~1.8 μm) and worn-out wire (~0.8 μm) side thin Si wafers, and this is considered to achieve sawing yields above 90% in the present study.